Evaluating the efficacy of urinary trypsinogen-2 Dipstick test in diagnosing acute pancreatitis (Panacea Journal of Medical Sciences, 2022)
Background: Acute Pancreatitis (AP) is a very common cause of acute abdomen in emergency department. The disease may vary from mild self-limiting symptoms to multi organ failure and has high mortality rate. Although most of the cases are treated by mild symptomatic treatment but severe cases require intensive monitoring, so early diagnosis and goal directed treatment is very essential to reduce mortality and morbidity of disease.Aims and Objective: The present study aims to know the efficacy of urinary trypsinogen-2 dipstick test in early diagnosis of acute pancreatitis.Materials and Methods: The prospective study sample included 98 patients who were presented to emergency department of Maharaja Krishna Chandra Gajapati Medical College & Hospital (MKCGMCH), Berhampur between August 2018 and July 2020 with acute severe pain abdomen suggestive of acute pancreatitis. Urine sample were obtained and results were recorded. Blood sample of all the patients were sent for serum amylase, lipase. Urinary Trypsinogen (UT)-2 dipstick test, based on principle of immunochromatographic, was done at the time of admission and serum amylase and lipase were sent for all patients. Serum Lipase was done through Calorimetric Method and Serum Amylase was done through Coupled Enzymatic Assay Method. Ultrasonography (USG) and Contrast-Enhanced Computed tomography (CECT) abdomen were sent after 4-5 days of admission and final diagnosis was made on the basis of CECT report.Results: Of 98 patients, 47 cases were final diagnosed to have acute pancreatitis. Sensitivity and specificity of Urinary Trypsinogen (UT)-2 was found to be 91.48% and 94.11% respectively and Positive Predictive Value (PPV) and Negative Predictive Value (NPV) was found to be 93.47% and 92.30% respectively. Sensitivity, specificity, PPV and NPV of Serum Amylase was found to be 76.5%, 74.5%, 74.5% and 74.5% respectively and similarly, sensitivity, specificity, PPV and NPV was found to be 80.85%, 72.5%, 73.1% and 80.4% respectively.Conclusion: Urinary Trypsinogen (UT)-2 Dipstick test has high sensitivity, specificity, PPV and NPV and therefore can be used reliably in emergency setting for diagnosis and thereby start a goal directed treatment and thus, reduce the mortality and morbidity of the disease.